Interaction of α-Agglutinin and a-Agglutinin, Saccharomyces cerevisiae Sexual Cell Adhesion Molecules - Zhao, Hui (American Society for Microbiology, 2001)
α-Agglutinin and a-agglutinin are complementary cell adhesion glycoproteins active during mating in the yeast Saccharomyces cerevisiae. They bind with high affinity and high specificity: cells of opposite mating types are irreversibly bound by a few pairs of agglutinins. Equilibrium and surface plasmon resonance kinetic analyses showed that the purified binding region of α-agglutinin interacted similarly with purified a-agglutinin and with a-agglutinin expressed on cell surfaces. At 20°C, the K(D) for the interaction was 2 × 10(−9) to 5 × 10(−9) M. This high affinity was a result of a very low dissociation rate (≈ 2.6 × 10(−4) s(−1)) coupled with a low association rate (= 5 × 10(4) M(−1) s(−1)). Circular-dichroism spectroscopy showed that binding of the proteins was accompanied by measurable changes in secondary structure. Furthermore, when binding was assessed at 10°C, the association kinetics were sigmoidal, with a very low initial rate. An induced-fit model of binding with substantial apposition of hydrophobic surfaces on the two ligands can explain the observed affinity, kinetics, and specificity and the conformational effects of the binding reaction.